2010
DOI: 10.1111/j.1744-7909.2010.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Acyl‐lipid Δ12‐desaturase Gene in Prokaryotic and Eukaryotic Cells and Its Effect on Cold Stress Tolerance of Potato

Abstract: We report the expression profile of acyl-lipid Delta12-desaturase (desA) gene from Synechocystis sp. PCC6803 and its effect on cell membrane lipid composition and cold tolerance in prokaryotic (Escherichia coli) and eukaryotic (Solanum tuberosum) cells. For this purpose, a hybrid of desA and reporter gene encoding thermostable lichenase (licBM3) was constructed and used to transform these cells. The expression of this hybrid gene was measured using qualitative (Petri dish test, electrophoregram and zymogram) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…RNA-seq transcriptomics analysis showed that slr1350 encoding acyl-lipid desaturase was up-regulated at 72 h. In a previous study, the acyl-lipid desaturase ( desA ) gene from Synechocystis sp. PCC6803 was expressed in prokaryotic ( E. coli ) and eukaryotic ( Solanum tuberosum ) cells, which led to an enhanced cold tolerance due to increased unsaturated fatty acid concentration in their lipids [32]. Several genes encoding cell envelope proteins were found induced by ethanol exposure (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…RNA-seq transcriptomics analysis showed that slr1350 encoding acyl-lipid desaturase was up-regulated at 72 h. In a previous study, the acyl-lipid desaturase ( desA ) gene from Synechocystis sp. PCC6803 was expressed in prokaryotic ( E. coli ) and eukaryotic ( Solanum tuberosum ) cells, which led to an enhanced cold tolerance due to increased unsaturated fatty acid concentration in their lipids [32]. Several genes encoding cell envelope proteins were found induced by ethanol exposure (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Geobacillus gargensis showed an increased synthesis of BCFAs and SCSFAs at 60-65°C, indicating an activation of branchedchain alpha-keto acid reductase (BCKR). At lower culture temperatures, desaturases are upregulated with an increase in unsaturated FAs (Amiri et al 2010). These changes reflect on the dynamic and physiological responses of G. gargensis subjected to variable temperature regimes.…”
Section: Effect Of Temperature On Fa Ratiomentioning
confidence: 99%
“…However as a response to high temperature, the denatured proteins increase in vivo , and Hsp60 binds to the denatured protein to maintain their soluble state. In the presence of Mg 2+ -ATP, Hsp60 can change folding proteins to refold into the active conformation, or degrade the denatured protein [35]. For example, Hsp60 can refold the Rubisco enzyme of cyanobacteria and malate dehydrogenase of mitochondrion in vitro [36].…”
Section: Discussionmentioning
confidence: 99%